Assessing China's solar power potential: Uncertainty quantification and economic analysis - Gege Yin; Xiaojia He; Qin, Yue; Lei Chen; Yuan Hu; Yu Liu; Zhang, Chuan (Resources, Conservation and Recycling, 2025)
Solar power is vital for China's future energy pathways to achieve the goal of 2060 carbon neutrality. Previous studies have suggested that China's solar energy resource potential surpass the projected nationwide power demand in 2060, yet the uncertainty quantification and cost competitiveness of such resource potential are less studied. Therefore, we applied an integrated framework to simulate China's solar photovoltaic (PV) technical potential, and incorporated potential uncertainty stemming from climate change, land use dynamics, and technological advancements. In addition, we constructed the solar energy supply curve for each province and calculated the economic potential. According to our results, approximately 78.6 % and 99.9 % of China's technical solar PV potential are priced lower than the benchmark price of coal-fired energy in pessimistic and optimistic scenario. These findings highlight the significant technical and economic potential of solar PV as a cost-effective alternative to coal-fired electricity to meet China's growing electricity demands.
Keywords: Economic potential; Large-scale solar PV; Supply curve; Technical potential; Uncertainty quantification